Synthesis and Antimicrobial Activity of 2-(Methyl Amino)-4-(4'-Ethoxy Anilino)-6-(Substituted Dihydrodino)-S-Triazines - Mane, D.V.; Shingare, M.S. (Asian Journal of Chemistry, 2010)
Cyanuric chloride and methyl amine in equimolar proportion were condensed and then treated with p-phenitidine in equimolar proportion to get the corresponding intermediate (I) which was further treated with various substituted dihydropyridines to get the corresponding 1,3 ,5-triazines (II). The compounds were tested for their antimicrobial activity. Some of the compounds show remarkable activity.